2000
DOI: 10.1002/1521-4079(200003)35:3<355::aid-crat355>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Hop-17(21)-en-3β-yl acetate of Pluchea pteropoda Hemsl. from Vietnam

Abstract: The title compound isolated from the roots of a Vietnamese plant and being known for its activity against fever was identified by this X‐ray analysis to be a pentacyclic triterpene of hopanoide type with a C17=C21 endocyclic double bond in the five membered ring. The presence of several axially substituted methyl groups on both the α and β side causes the so called "mid‐molecule strain" having already been reported in the literature for other hopane type ring systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Regarding these aspects, the invariom formalism is properly suited for further application not only in traditional medicine, which is frequently part of the public health system (Luger et al, 2000;Kingsford-Adaboh et al, 2001, but also as an affordable tool in general drug research.…”
Section: Tablementioning
confidence: 99%
“…Regarding these aspects, the invariom formalism is properly suited for further application not only in traditional medicine, which is frequently part of the public health system (Luger et al, 2000;Kingsford-Adaboh et al, 2001, but also as an affordable tool in general drug research.…”
Section: Tablementioning
confidence: 99%
“…Hopen-3-ones, including hop-17(21)-and/or -22(29)-have been found in leaves of Euphorbia lathyris [69] in Maprounea guianensis from Brazil [70], in Gentianaceae family plants in China [71], in the Quercus species in Hong Kong [72,73], and in peatland topsoil in a French bog study [26]. The methyl ether derivative of the hopanoid -22(29)-has been isolated from the epicuticular waxes of a graminea -Chionochloa- [74] while its acetyl derivative has been isolated from a Vietnamese Asteraceae plant [30].…”
Section: Hopanoid Derivatives In the Peat Extractsmentioning
confidence: 99%
“…Among the few records of triterpenyl acetates in sediments, it can be mentioned those recorded in a peatland topsoil with an acetate group at C-3 and with oleanane, ursane, friedelane, and isobauerane skeleton [26], and their MeO counterparts that have been recorded in Gramineae [27] and in turf and related lake sediments [28,29]. Bauerenyl and hopenyl with an acetate group at C-3 have also been recorded in Asteraceae plants [30,31] and hopenyl and lupenyl acetates have been detected in large amounts in propolis extracted from beehives [32,33]. The present study focuses on the variation in concentrations of triterpenyl acetates in various peat profiles from the North of Spain with the aim of establishing the conditions under which natural acetylation might occur in Asturian Sphagnum peat environments.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that methanol extracts from barks and leaves of P. pteropoda showed certain antibacterial activity (Yuliani et al 2015). In Vietnam, P. pteropoda has long been used as a folk medicinal herb, often used to treat fevers (Luger et al 2000). So far, only the cp genome of P. indica has been reported in the genus Pluchea.…”
mentioning
confidence: 99%
“…In Vietnam, P. pteropoda has long been used as a folk medicinal herb, often used to treat fevers (Luger et al. 2000 ). So far, only the cp genome of P. indica has been reported in the genus Pluchea .…”
mentioning
confidence: 99%